Analysis of Vulnerability Levels to the Flash Flood Based on Social Economic and Institutional Factors in Wasior, Teluk Wondama, West Papua - Baharinawati Wilhan Hastanti; Freddy Jontara Hutapea (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2020)
One form of disaster mitigation is to know the vulnerability of areas that are at risk of disaster socially and economically. Studies on vulnerability to flash floods are necessary, as it might prevent material losses and fatalities. Wasior District at Teluk Wondama Regency experienced a flash flood in 2010 causing negative impacts such as fatalities and large material losses. To anticipate flash floods that might occur in the future, studies to evaluate the vulnerability to the flash flood are needed. This study aimed to: 1) analyze the level of vulnerability to flash floods in Wasior based on socioeconomic factors post the 2010 flash floods, 2) analyze the level of vulnerability to flash floods in Wasior based on institutional factors. The method used in this study was a combination of qualitative and quantitative methods. Data collection was conducted by observation, interview, and documentation. Data were analyzed by: 1) identifying the socioeconomic indicators of the community and institutions around the watershed, 2) providing weighting scores to the social economic criteria and institutional criteria from the most vulnerable to the least vulnerable, 3) assessing the level of community and institution vulnerabilities in the study site to the impact of flash floods based on the calculation of the weighting scores of socio-economic and institutional indicators. The results showed that the level of socioeconomic vulnerability to flash floods were categorized as moderate (total score 2.084), while the level of institutional vulnerability was low (total score 2.251). The results of this study can be used as a basis for considerations in the implementation of flash flood mitigation in Wasior.Keywords: vulnerabilities, social, economic, institutional, flash flood